2023
DOI: 10.1177/15589250231152591
|View full text |Cite
|
Sign up to set email alerts
|

Review on the design and application of concrete canvas reinforced with spacer fabric

Abstract: Concrete canvas reinforced with spacer fabric has increasingly gained popularity due to its lightweight, great flexibility, high strength and low contamination compared to ordinary concrete. In order to fully explore the structure and performance of this novel composite, this review illustrates how to design high-performance concrete canvas and presents a summary of recent application status of it. Firstly, the structure and properties of knitted and woven spacer fabric and concrete material that comprise conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…Therefore, it is possible for UHMWPE to replace some common fibers for reinforcing concrete specimens. Some studies have shown that, in concrete canvas structures, the tensile strength and flexural strength of CNT-modified UHMWPE are 3 to 3.8 times greater than those of ordinary fabrics [25,164]. Due to its unique macromolecular structure, UHMWPE has a low density but high modulus, which allows it to exhibit mechanical properties comparable to those of metals or ceramics [170].…”
Section: Advantages Of Uhmwpe Over Other Frpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible for UHMWPE to replace some common fibers for reinforcing concrete specimens. Some studies have shown that, in concrete canvas structures, the tensile strength and flexural strength of CNT-modified UHMWPE are 3 to 3.8 times greater than those of ordinary fabrics [25,164]. Due to its unique macromolecular structure, UHMWPE has a low density but high modulus, which allows it to exhibit mechanical properties comparable to those of metals or ceramics [170].…”
Section: Advantages Of Uhmwpe Over Other Frpsmentioning
confidence: 99%
“…Among the various types of FRPs, Ultra-High Molecular Weight Polyethylene (UHMWPE) stands out for its exceptional properties and potential in concrete repair [25][26][27][28]. UHMWPE is a polymer formed from a large number of repeated ethylene units [26,29,30], characterized by its high tensile strength [31], elongation [32], good wear resistance [33], and energy absorption capabilities [34].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this prevents the necessity for conventional procedures such as blending, molding, and extracting (Li et al, 2019). The applications of this material vary from in atable tents and ditch lining to slope protection, building restoration, and reinforcement (Ding et al,2020;Jafari et al, 2020;Ding et al,2022;Liu et al, 2023;Eller et al, 2023;Xiang et al, 2023. In comparison to traditional materials used for slope protection layers, such as shotcrete layers, GCCMs offers easier, and more costeffective installation process, providing substantial bene ts like reduced environmental impact, shortened construction periods, and lower labor costs. Furthermore, it is effectiveness in rapidly constructing slope protection, such as emergency slope protection or heavy rainfall (Li et al 2016;Zhang 2020).…”
Section: Introductionmentioning
confidence: 99%
“…En el artículo Revisión sobre el diseño y aplicación de lona de concreto reforzado con tela espaciadora, (Liu et al 2023), indica en relación a las características de la lona de concreto, se revisas sus aplicaciones actuales en áreas como carpas de emergencia en casos de desastre, protección de taludes y revestimiento de drenaje. Sin embargo, es importante destacar que las aplicaciones prácticas de este material aún se encuentran en etapa inicial.…”
Section: Tablaunclassified